Left permutable multiplicative sets and left strongly prime ideals in rings - Kaučikas, Algirdas (Lietuvos matematikos rinkinys, 2008)
Left permutable multiplicative sets S for an associative ring R are defined. Particularly, this notion includes commutative multiplicative sets of the associative ring. We also define the notion of the left S-ideal and prove, that each left S-ideal, maximal with respect to being disjoint from S, is left strongly prime.
Keywords: (left) strongly prime ideal; insulator; multiplicative set; left strongly prime radical